2016
DOI: 10.1016/j.neuropsychologia.2016.02.026
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetrical influence of increasing time-on-task on attentional disengagement

Abstract: Increasing time-on-task leads to fatigue and, as shown by previous research, differentially affects the deployment of visual attention towards the left and the right visual space. In healthy participants, an increasing rightward bias is commonly observed with increasing time-on-task. Yet, it is unclear whether specific mechanisms involved in the spatial deployment of visual attention are differentially affected by increasing time-on-task. The aim of the present study was to investigate whether prolonged time-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…It has been suggested that rightward shifts in spatial attention with time‐on‐task occur due to an interaction between spatial and non‐spatial aspects of attention such as alertness/fatigue (Manly et al ., ; Fimm et al ., ; Dufour et al ., ; Paladini et al ., , ; see also Newman et al ., , ). In Corbetta & Shulman's () neuroanatomical attention model, depletion of the primarily right lateralized ‘alertness’ network (Sturm & Willmes, ) results in decreased recruitment of the RH dorsal frontoparietal attention network (DAN) which would be expected to reduce pseudoneglect, that is to induce a rightward shift in spatial bias.…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that rightward shifts in spatial attention with time‐on‐task occur due to an interaction between spatial and non‐spatial aspects of attention such as alertness/fatigue (Manly et al ., ; Fimm et al ., ; Dufour et al ., ; Paladini et al ., , ; see also Newman et al ., , ). In Corbetta & Shulman's () neuroanatomical attention model, depletion of the primarily right lateralized ‘alertness’ network (Sturm & Willmes, ) results in decreased recruitment of the RH dorsal frontoparietal attention network (DAN) which would be expected to reduce pseudoneglect, that is to induce a rightward shift in spatial bias.…”
Section: Discussionmentioning
confidence: 90%
“…These spatial and non-spatial aspects of attention are thought to interact with each other, whereby non-spatial attention can modulate the deployment of visual attention in space. In fact, previous research has shown that, with a reduced level of alertness (triggered by different manipulations, such as sleep deprivation, circadian rhythmicity, or increasing time-on-task), healthy participants typically show a rightward shift when deploying visual attention in space (e.g., Manly et al 2005 ; Fimm et al 2006 ; Dufour et al 2007 ; Heber et al 2008 ; Matthias et al 2009 ; Benwell et al 2013 ; Newman et al 2013 ; Dorrian et al 2015 ; Paladini et al 2016 ). However, to date, the neural basis of this interaction between spatial and non-spatial attentional aspects is poorly understood, and the neurophysiological substrate of the above-mentioned rightward attentional shift with a reduced level of alertness is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Two papers included in this special issue analysed eye movements in order to assess the effects of a manipulation of non-spatial attentional aspects (i.e., fatigue or decreasing arousal) on the spatial deployment of visual attention. Paladini, et al (2016) manipulated the level of fatigue in healthy individuals by means of increasing time-on-task, and measured spatial attentional deployment by means of a saccadic paradigm, in which horizontal left-and right-sided saccades had to be produced. The authors showed that, with increasing time-on-task and fatigue, the attentional deployment was affected asymmetrically, in that attentional disengagement costs became significantly lower for rightward than for leftward saccades.…”
Section: Deployment Of Visual Attentionmentioning
confidence: 99%
“…A direct comparison of the paradigms applied by Paladini et al (2016) and Fimm et al (2016) reveals at least two central differences: i) the type of manipulation of non-attentional aspects, i.e., increasing fatigue due to increasing time on task vs. decreasing arousal due to sleep deprivation; and, ii) the amount of trials administered during a testing session (with lateralized effects on attentional disengagement seeming to appear only after a conspicuous amount of trials). Overall, the results seem thus to support the idea that eye movement analysis can reveal interactions between nonspatial attentional aspects and spatial ones.…”
Section: Deployment Of Visual Attentionmentioning
confidence: 99%